From Defense to Resilience: Environmental Security beyond Neo‐liberalism. Issue 3 (September 2014) - Corry, Olaf
<x xml:space="preserve">Abstract</x> While the rise of "resilience" as a strategic concept has been widely noted, critical security scholars have given it a frosty reception, viewing it as a vehicle and multiplier of neo‐liberal governmentality. This article acknowledges that resilience does form part of a neo‐liberal security regime, but argues that a shift from defense to resilience is not devoid of critical potential, and develops recent calls for critique to be made more context specific. It begins by arguing that blanket condemnation of resilience is part of a wider tendency to apply Foucault's "governmentality" concept as a particular global form of power, rather than as an empirically sensitive analytic framework open to different configurations of power. It then shows how resilience also forms part of a strategy to manage uncertainty—particularly in relation to coping with global environmental risks—which directly challenges neo‐liberal nostrums. A comparison with the concept of "defense" is made, arguing that resilience, while problematic for other reasons, potentially avoids the pernicious us‐them logic, exceptionalism, and short‐termism characteristic of defense strategies.